ESA (EXERCISE AND SELF-AFFIRMATION) ON IMPROVING FUNCTIONAL STATUS OF HEMODIALYSIS PATIENTS - Mardiyah, Adiyati; Anggorowati; Johan , Andrew; Maktum, Ummi; Julianti , Erna (Jurnal Ilmiah Keperawatan, 2024)
The hemodialysis process is essential for patients with chronic kidney disease to maintain their lives. However, this routine and continuous process can cause complications in the body. Patients undergoing hemodialysis experience changes in functional status across physical, psychological, social, and environmental health domains. This study was carried out to determine the effect ESA (Exercise and Self-Affirmation) intervention on the functional status of patients with chronic kidney disease. Previous studies show that physical exercise combined with self-affirmation interventions can improve mood and cognitive function. Self-affirmation has been shown to reduce depression levels, improve sleep quality, enhance social participation, and ultimately improve the quality of life. This study used a quasi-experimental design with a pretest-posttest control group, involving thirty- nine patients in the control group and thirty-nine patients in the intervention group at the hemodialysis unit of PKU Muhammadiyah Yogyakarta. Functional status was assessed using the SF- 36 questionnaire and analyzed using paired t-tests for paired groups and independent t-tests for unpaired groups. The average SF-36 score before the ESA intervention was 44.53, and the average score after the intervention was 69.37. The t-test results showed a significance value of 0.000 (p<0.05). These results show a significant difference between the pretest and posttest results in the intervention group after the ESA intervention. In conclusion, the ESA intervention can improve the functional status of hemodialysis patients, so that their physical and mental function is better. The ESA intervention positively affects the functional status of patients with chronic kidney disease undergoing hemodialysis.